PENGEMBANGAN MEDIA PARU-PARU BUATAN BERBASIS MANEKIN PADA MATERI SISTEM PERNAPASAN MANUSIA - Lukman Nulhakim; Encep Andriana; Dhika Anggi Sandika (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports the development of a mannequin-based artificial lung learning media to find out how fifth-grade students respond at SDN Merak II to use the media. The research indicates the assessment results from media experts obtain an average percentage score of 91.10% in the "Very Feasible" criteria. In addition, the assessment results from material experts obtain an average final score percentage of 88.64% in the "Very Feasible" criteria. If the achievement of the expert validation assessment results was calculated, it can be said that this mannequin-based artificial lung mediaachieved a feasibility test score with an average score of 89.87% through an expert validation test and obtained the "Very Feasibility" category. The results of students’ responses on the development of mannequin-based artificial lung media achieved an average score of 91,36% in the "Very Good" category.